Occurrence of IgA and IgG autoantibodies to calreticulin in coeliac disease and various autoimmune diseases - Sánchez, D; Tucková, L; Sebo, P; Michalak, M; Whelan, A; Sterzl, I; Jelínková, L; Havrdová, E; Imramovská, M; Benes, Z; Krupicková, S; Tlaskalová-Hogenová, H (Journal of autoimmunity, 2000)
Calreticulin (CRT), a high-affintiy calcium binding protein and chaperone, was recently identified as one of the targets of autoantibodies in coeliac disease. We evaluated the level of IgA and IgG antibodies to CRT in sera from patients with coeliac disease and various autoimmune diseases. The level of antibodies to gliadin (shown previously to cross-react with CTR), isolated enterocytes and tissue transglutaminase were determined for comparison. The mean level of IgA antibodies to CRT was significantly higher (P< 0.001) in sera from coeliac patients with active disease (139.9+/-11.2 AU/+/-SE) than in healthy controls (20.9+/-1.7 AU). In sera of patients with systemic lupus erythematosus (SLE), insulin dependent diabetes mellitus (IDDM), multiple sclerosis (MS) and autoimmune thyroiditis (AT) or inflammatory bowel disease (IBD) the mean level (25.8+/-3.7 to 38.1+/-5.6 AU) did not exceed the cut-off value. A low level of these antibodies, however, was detected in some sera of patients with MS and IBD. The level of IgG anti-CRT antibodies was increased in coeliac patients (mean 125.4+/-8.0 AU, P< 0.001) when compared to that in healthy controls (33.9+/-2.3 AU). The IgG anti-CRT antibodies were also detected in about 30% of SLE patients sera (54.1+/-3.6 AU, P< 0.001), but the mean level reached only half that detected in coeliac patients.
Keywords: Autoantibodies; Calreticulin; autoimunitní nemoci; Humans; lidé středního věku; imunoglobulin G; dítě; Child; Calcium-Binding Proteins; Aged; ribonukleoproteiny; dospělí; Blotting, Western; ELISA; senioři; lidé; Immunoglobulin A; Enzyme-Linked Immunosorbent Assay; Autoimmune Diseases; předškolní dítě; Adult; celiakie; autoprotilátky; Middle Aged; Adolescent; proteiny vázající vápník; kalretikulin; Celiac Disease; imunoglobulin A; western blotting; Immunoglobulin G; Child, Preschool; Ribonucleoproteins; mladiství